Principal Leadership and its Impact on Teacher Performance: a Case Study of Elementary School in Banda Aceh - Nuhari, Insan; Jalaluddin, Jalaluddin; Salfiyadi , Teuku (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study objectives to examine the influence of principal leadership on teacher performance at SD Negeri 10 Banda Aceh. The research employed a descriptive qualitative approach, involving the principal and 16 teachers as study subjects. Data was collected through interviews and questionnaires to get insight into the individuals' perceptions and experiences. To identify trends in responses, the obtained data was analysed using a percentage-based method. The findings revealed that teacher responses regarding the principal’s leadership were consistently high, with responses categorized as "continuously," "frequently," and "occasionally" each receiving 100%. Overall, the analysis showed that 93.75% of the teachers indicated a strong correlation between principal leadership and teacher performance.